The Effect of Moringa Oleifera Leaves Plus Royal Jelly Supplement on Cortisol Hormone and Stress Levels on Anemia of Pregnant Women in Takalar Regency - Wilma Florensia P; Veni Hadju; Masyitha Muis; Citrakesumasari Citrakesumasari; Saifuddin Sirajuddin; Andi Zulkifli (Newinera Publisher, 2020)
This study aims to determine the effect of Moringa Oleifera plus Royal Jelly leaf extract supplements on stress levels and cortisol levels in anemic pregnant women. This study was a true experimental study with a controlled randomized double blind pretest-post test design. The subjects of this study were 44 pregnant women with anemia, taken based on inclusion and exclusion criteria and divided into two groups, namely the group given moringa capsules (n = 22) and moringa capsules plus royal jelly (n = 22). Data were analyzed using Chi-square test, Paired T-Test, Wilcoxon and Independent T-Test using SPSS. The result of the study shows a significant decrease in the stress level in the royal jelly moringa group from 29.23 ± 10.451 to 17.00 ± 6.325 with a value of P = 0.000 and in the moringa group from 23.59 ± 8.110 to 18.05 ± 4.498 with a value of P = 0.022. Likewise, the cortisol levels decreased significantly in the moringa royal jelly group from 41.17 ± 18.466 to 28.75 ± 15.024 with a P value = 0.002 and the moringa group from 34.54 ± 21.437 to 24.70 ± 18.218 with a P value = 0.009. However, the difference in the magnitude of change did not differ significantly for stress levels and cortisol levels (P> 0.05). It is concluded that the reduction in stress and changes in royal jelly moringa tends to be greater than that of moringa.